COVID-19 is shifting consumption and disrupting dairy value chains in Ethiopia - Tesfaye, Agajie; Habte, Yetimwork; Minten, Bart (International Food Policy Research Institute, 2020)
The COVID-19 crisis is having a range of impacts on food consumption and value chains everywhere — containment measures, lost incomes, and perceptions of disease risk are food altering availability and consumer preferences. To understand the effects of the COVID-19 crisis on Ethiopia’s important dairy sector, we conducted a qualitative appraisal of the dairy value chain supplying Addis Ababa. Between April 15 and May 10, we interviewed nearly 100 commercial and small dairy farmers in urban and rural areas, dairy processors, traders, development agents, urban retailers, and consumers. Overall, the survey indicates that the Ethiopian dairy sector has experienced only moderate impacts — especially compared to the livestock sectors in China and other countries. However, certain segments of the industry — particularly raw milk vendors and small dairy shops — have been hit hard.